2016
DOI: 10.15283/ijsc.2016.9.1.145
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bone Marrow Mononuclear Cells on Lung Regeneration and Apoptosis in a Simple Model of Pulmonary Emphysema

Abstract: BackgroundIn severe chronic stages of emphysema the only treatment is lung transplantation. SO, an urgent need exists for the development of effective treatments. Stem cells therapy arises as a new therapeutic approach.Aim of the WorkTo investigate whether bone marrow mononuclar cells (BMMNCs) can promote lung regeneration and decrease apoptosis in lipopolysaccharide (LPS) induced pulmonary emphysema in C57Bl/6 mice.Material and Methods14 weeks old female mice (C57Bl/6), weighing around 25 g were used in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In addition to the effects of TGF-β on silica-induced lung fibrosis, the increased apoptotic cell counts in lung parenchyma have been correlated to increased TGF-β levels [ 11 , 27 , 37 ]. Some studies that carried out BMMCs transplantation have demonstrated anti-apoptotic effects in different experimental models [ 38 , 39 ], and a previous study from our group has shown that repeated administration of bone marrow-derived cells reduced mRNA expression of pro-caspase 3, as well as apoptotic cell counts in lung parenchyma and granulomas [ 40 ]. Here, we have observed that both BMMC-healthy and BMMC-sil reduced apoptotic cell counts in the lung parenchyma, but not in granulomas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the effects of TGF-β on silica-induced lung fibrosis, the increased apoptotic cell counts in lung parenchyma have been correlated to increased TGF-β levels [ 11 , 27 , 37 ]. Some studies that carried out BMMCs transplantation have demonstrated anti-apoptotic effects in different experimental models [ 38 , 39 ], and a previous study from our group has shown that repeated administration of bone marrow-derived cells reduced mRNA expression of pro-caspase 3, as well as apoptotic cell counts in lung parenchyma and granulomas [ 40 ]. Here, we have observed that both BMMC-healthy and BMMC-sil reduced apoptotic cell counts in the lung parenchyma, but not in granulomas.…”
Section: Discussionmentioning
confidence: 99%